Helicobacter pylori induces a novel form of innate immune memory via accumulation of NF-кB proteins - Frauenlob, Tobias; Neuper, Theresa; Regl, Christof; Schaepertoens, Veronika; Unger, Michael S.; Oswald, Anna-Lena; Dang, Hieu-Hoa; Huber, Christian G.; Aberger, Fritz; Wessler, Silja; Horejs-Hoeck, Jutta (Frontiers in Immunology, 2023)
Helicobacter pylori is a widespread Gram-negative pathogen involved in a variety of gastrointestinal diseases, including gastritis, ulceration, mucosa-associated lymphoid tissue (MALT) lymphoma and gastric cancer. Immune responses aimed at eradication of H. pylori often prove futile, and paradoxically play a crucial role in the degeneration of epithelial integrity and disease progression. We have previously shown that H. pylori infection of primary human monocytes increases their potential to respond to subsequent bacterial stimuli – a process that may be involved in the generation of exaggerated, yet ineffective immune responses directed against the pathogen. In this study, we show that H. pylori-induced monocyte priming is not a common feature of Gram-negative bacteria, as Acinetobacter lwoffii induces tolerance to subsequent Escherichia coli lipopolysaccharide (LPS) challenge. Although the increased reactivity of H. pylori-infected monocytes seems to be specific to H. pylori, it appears to be independent of its virulence factors Cag pathogenicity island (CagPAI), cytotoxin associated gene A (CagA), vacuolating toxin A (VacA) and γ-glutamyl transferase (γ-GT). Utilizing whole-cell proteomics complemented with biochemical signaling studies, we show that H. pylori infection of monocytes induces a unique proteomic signature compared to other pro-inflammatory priming stimuli, namely LPS and the pathobiont A. lwoffii. Contrary to these tolerance-inducing stimuli, H. pylori priming leads to accumulation of NF-кB proteins, including p65/RelA, and thus to the acquisition of a monocyte phenotype more responsive to subsequent LPS challenge. The plasticity of pro-inflammatory responses based on abundance and availability of intracellular signaling molecules may be a heretofore underappreciated form of regulating innate immune memory as well as a novel facet of the pathobiology induced by H. pylori.